Voltage Stability Enhancement by Coordination of SVC and TCSC Using Particle Swarm Optimization - Pandya, Maulik; Jamnani, J. G. (Asian Journal of Electrical Sciences, 2019)
The Flexible AC Transmission System (FATCS) plays a vital role in power system performance enhancement. They attributes to accomplish faster and having answers for many issues in power system study. With regards to this, a particles warm optimization (PSO) algorithm is implemented so that to design the coordinated parameters of static VAR compensator (SVC) and Thyristor Controlled Series Capacitor (TCSC). Transient stability of a power system is based on the generator relative rotor angles obtained from time domain simulations outputs. A self-sufficient model of IEEE fourteen bus systems has been given with full detail and voltage stability analysis is done by considering load changing at a bus. PSO applied here is built on searching the values of L and C of SVC, then one can achieve desired and fine coordination. PSO is available with few modification, as change in PSO range & number, difference in selection criteria technique, control technique etc, with due respect to normalize PSO. The results are compared and found that coordination of FACTS devices with each other promises the efficiency of the suggested method for revamping Power flows. When function of TCSC is impelled by some curb, adjustable SVC can supply additional support to upgrade the gross performance.